A Study on the Decontaminated Efficiency of Ultraviolet Device on the Indoor Airborne Bacteria. (2017) - Li, Yanju; Wang, Min; Guan, Dexing; Lv, Haoqi; Zhao, Jiuwei; Yu, Xiaojuan; Yang, Xiaoguang; Wu, Chunbin
Abstract: The aims of this paper were studied bactericidal effect of the ultraviolet lamp on irradiation intensity, irradiation time and installation height. Three independent variables were set, such as irradiation intensity, irradiation time and installation height. By natural sedimentation method, the airborne bacteria were sampled before and after radiation of ultraviolet lamp, then the decay rates of airborne bacteria were calculated. The decontaminated efficiency were more than 40% when irradiation power of UV were 30w (42.5%) and 40w (60%). With the lengthen irradiation time, the better reduced rate of the airborne bacteria. The bactericidal effect of the ultraviolet lamps was in proportion to their irradiation intensity and in inverse proportion to their installation height. According to the actual circumstance of university cafeteria, the arrangement of ultraviolet lamp was that irradiation intensity was 40W, installation height was 2.0m, and irradiation time was 60min.